Time To Go? Head Coach Quits and Dismissals in Professional Football - Babatunde Buraimo; Alex Bryson; Rob Simmons (Institute of Labor Economics (IZA), 2017)
That football Head Coaches will be dismissed for poor performance and will quit when they have better outside options seems to be nothing more than a statement of the obvious. But owners may find it hard to distinguish poor performance from bad luck and may find it difficult to identify and attract talented managers from other clubs. Indeed, most of the literature indicates little improvement in team performance when one coach replaces another. Equally, Head Coaches may have few options to move to better clubs even when they are performing well. We identify significant differences between determinants of quits and dismissals that are largely consistent with a standard model which predicts departures occur when the value of the job match specific surplus for one or both parties falls below the value of outside options. However, dismissals and quits are more common in Italy and Spain than in Germany and France, suggesting institutions may be important. We discuss the implications of our findings in the context of principal-agent theory and the wider literature on turnover among CEOs and other corporate leaders.
Keywords: J23; J24; J63; J64; 330; quits; dismissals; layoffs; managerial performance; team performance; football; survival analysis; competing risks